The Development of Interactive Media Using Canva Application to Improve English Learning Outcomes of Fifth Grade Students - Aisah (Journal of Applied Linguistics, 2025)
This study aims to develop interactive media using the Canva application for English instruction, targeting the enhancement of learning outcomes for fifth grade students at SD Negeri 050771 Pangkalan Susu. The background of this research highlights the need for effective educational tools to improve students engagement and performance in English. Employing a Research and Development (R&D) approach, the study utilized the ADDIE development model, which encompasses five stages: Analysis, Desin, Development, Implementation, and Evaluation. The research was conducted with 28 fifth grade students, consisting of 15 boys and 13 girls. Data collection methods included observation, interviews, tests, and documentation to assess the efectiveness of the developed media. Expert evaluations indicated that the interactive media received scores of 82% from material experts, 80% from language experts, and 82% from media experts, all categorized as “ feasible”. The results showed a significant improvement in students performance, during the pre test, only 42% of students achieved completion, with 12 passing and 16 not completing the test. In contrast, the post test results revealed an increase in the completing rate to 82%, with 23 students successfully funishing the test and only 5 not completing it. In conclusion, the findings suggest that the interactive media developed using the Canva application for the English subject has effectively improved the learning outcomes of fifth grade students at SD Negeri 050771 Pangkalan Susu. Keywords : Interactive media, Canva application, Learning outcomes